Potensi lokal sebagai upaya pengentasan kemiskinan di Desa Srigading Kecamatan Lawang Kabupaten Malang - Muhroni, Tedy; Bimajati, Tiara Arya Putri (Maliki Interdisciplinary Journal, 2025)
Srigading Village, Lawang Subdistrict, Malang District, has great potential in local product development. This research aims to identify and analyze the local potential that can be developed as an effort to alleviate poverty in Srigading Village, Lawang Subdistrict, Malang District. Through a qualitative approach, this research involved in-depth interviews with the community, community leaders, and officials of Srigading Village, Lawang Sub-district, Malang District. The results showed that Srigading Village has abundant natural resource potential, such as agriculture, livestock, and tourism. This research analyzes the role of two superior products, namely cow’s milk products and coffee processing in Srigading Village, Lawang Subdistrict, Malang Regency, in alleviating poverty through community empowerment, local economic improvement, and integrated development strategies. The results of the analysis show that optimizing the potential of cow’s milk and coffee is able to significantly increase the income of the village community. This research suggests several local potential development strategies, such as the formation of joint business groups, skills training, and product marketing. Thus, it is expected to improve community welfare and reduce the poverty rate in the village.